2020
DOI: 10.3390/plants9091126
|View full text |Cite
|
Sign up to set email alerts
|

Communities of Fungi in Black Cherry Stumps and Effects of Herbicide

Abstract: So far, there have been no studies on fungal communities in Prunus serotina (black cherry) wood. Our objectives were to characterize fungal communities from P. serotina wood and to evaluate effects of glyphosate (Glifocyd 360 SL) used on P. serotina stumps on abundance, species richness and diversity of those communities. In August 2016, in the Podanin Forest District, stumps of black cherry trees left after felling were treated with the herbicide. Control stumps were treated with water. Wood discs were cut fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Although most Colletotrichum species were destructive pathogens [50], some members such as Colletotrichum tofieldiae colonized in Arabidopsis roots and transferred phosphorus to the host under phosphate deficiency conditions to promote plant growth [51], and Colletotrichum siamense had growth-promoting effects and suppressed Fusarium oxysporum symptoms in tomato plants [52]. A saprophytic yeast known as Colacogloea was highly competitive, tolerant of harsh environments, and non-pathogenic to humans, animals, or plants [53]. Spizellomyces may have more extensive pathways that help metabolize nutrients that were typically hard to obtain, boosting adaptability to a variety of environments [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most Colletotrichum species were destructive pathogens [50], some members such as Colletotrichum tofieldiae colonized in Arabidopsis roots and transferred phosphorus to the host under phosphate deficiency conditions to promote plant growth [51], and Colletotrichum siamense had growth-promoting effects and suppressed Fusarium oxysporum symptoms in tomato plants [52]. A saprophytic yeast known as Colacogloea was highly competitive, tolerant of harsh environments, and non-pathogenic to humans, animals, or plants [53]. Spizellomyces may have more extensive pathways that help metabolize nutrients that were typically hard to obtain, boosting adaptability to a variety of environments [54].…”
Section: Discussionmentioning
confidence: 99%
“…Within the Ascomycota, Cephalotrichum is a saprophytic soil fungus [72]; Myrmecridium, a plant endophytes taxon, has been reported to produce extracellular hydrolytic enzymes and cellulase [73]; Podospora are well-known cellulose degraders [74]; Nigrospora has the capacity to improve the withstand stress of host plants and produce antifungal compounds [75]; and Gibellulopsis is linked to carbohydrate content [76]. Within the Basidiomycota, members of Saitozyma are involved in the decomposition of dead plant biomass [77]; Colacogloea is a saprophytic yeast that can persist in difficult conditions [53]. Within the Mortierellomycota, Mortierella is mostly composed of saprophytic species that perform several functions, including the degradation of cellulose and lignin [78].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, decreased colonization of herbicide-treated stumps relative to the formulation, inoculum, and untreated stumps may be due to a less favorable environment for these fungi. Korzeniewicz et al [ 31 ] found higher levels of colonization by basidiomycete fungi in untreated black cherry stumps larger than 5 cm in diameter than in stumps treated with glyphosate. Our results showed no differences between the treatments for the number of sprout clumps and sprout height among the biological controls, the formulation-only treatments, and the untreated tanoak and bay laurel stumps.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Glyphosate had a profound inhibitory effect on isolate 19, where a higher dose of Glyphosate would result in a higher loss of colony diameter. According to [22] Glyphosate affect the diversity and abundance of fungal communities in deciduous tree wood. Another example, doses and incubation time of Triasulfuron herbicide has no consistent effect on relative abundance of the four microbial groups at the three soil treatments [23].…”
Section: Glyphosate (Herbicide)mentioning
confidence: 99%